KEEFEKTIFAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN MENGIDENTIFIKASI UNSUR – UNSUR DRAMA SISWA KELAS VIII SMP NEGERI 2 TALANG KELAPA - Oktaviani, Anis; Nuzulia Armariena, Dian; Nufus, Hayatun (Parataksis: Jurnal Bahasa, Sastra, dan Pembelajaran Bahasa Indonesia, 2023)
This study aims to determine the learning outcomes of class VIII students at SMP Negeri 2 Talang Kelapa by using the Problem Based Learning model. In this study, data collection used test techniques. This is evident from the calculation of student learning data using the t-test contained in the SPSS V26 program. Through the calculations that have been carried out on the t-test the significant value obtained is 0.917 which means that the significant value is > 0.05. The average value in the experimental class was 97 and the control class was 85. Calculation of the hypothesis using the t-test (Independent sample test) formula, namely tcount = 1.334 > tcount 1.332 with df 29. Thus Ho is rejected and Ho is accepted. So the researchers came to the conclusion that "The Problem Base Learning Model on the Ability to Identify Dramatic Elements of Class VIII Students of SMP Negeri 2 Talang Kelapa Has an Influence". Keywords: Problem Based Learning, Elements of Drama